KEBUTUHAN AIR BERSIH PENDUDUK KOTA BANDA ACEH - Nur Ismi Irwan; Abd. Jamal (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThis study aims to analyze the clean water needs of the residents of Banda Aceh. The variables arethe consumption of PDAM water, the income of household heads, the number of family members,the price of PDAM water and not PDAM, the presence or absence of other water sources besidesPDAM and water quality according to respondents' perceptions. Primary data were obtaineddirectly from the first party or respondents through direct interviews and in depth interviews. Thefindings show that the higher the household income, the less dependence of households on cleanwater sources from PDAM. In addition, the level of dependency on PDAM water tends to be inhouseholds with more family members. From the findings, it is known that very few residents ofBanda Aceh City use PDAM as a source of drinking water. The percentage is 3 percent ofrespondents which consist respondents with a large family membership and elderly women whoseincome tends to be small. PDAM as a Regional Drinking Water Company is expected to be able tochannel water flowing into high quality household connections pipes and can be drunk directly bythe community.Keywords: Clean Water Needs, Income, Number of Family Members, Water Prices, Water Quality